2012
DOI: 10.1111/j.1750-3841.2011.02608.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Chopping Conditions for Alaska Pollock, Pacific Whiting, and Threadfin Bream Surimi Paste and Gel based on Rheological and Raman Spectroscopic Analysis

Abstract: Chopping conditions to determine gel quality and manufacture surimi seafood are varied by all manufacturers. This paper covering three primary species for surimi with their suggested optimum chopping conditions: 15 min for Alaska pollock when chopped at 0 °C, 15 min for Pacific whiting at 15-20 °C, and 18 min for threadfin bream at 25-30 °C. The use of optimum chopping condition should maximize the value of each surimi and provide consistent quality to the end users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
(40 reference statements)
3
32
0
Order By: Relevance
“…G 0 declined after heating beyond 66 to 70°C. The decreased G 0 beyond this point was likely due to slipperiness of the gel between the cone and plate (Poowakanjana, Mayer, & Park, 2012).…”
Section: Rheological Properties Influenced By Nfbmentioning
confidence: 96%
“…G 0 declined after heating beyond 66 to 70°C. The decreased G 0 beyond this point was likely due to slipperiness of the gel between the cone and plate (Poowakanjana, Mayer, & Park, 2012).…”
Section: Rheological Properties Influenced By Nfbmentioning
confidence: 96%
“…Although winter surimi was less thermally stable than summer surimi (Figure ), α‐helical structure of the winter surimi kept almost unchanged during the chopping process. Poowakanjana et al () reported similar result that the helical structure of amide III of Alaska pollock surimi under chopping at 10°C for 21 min slightly decreased ( p > .05) compared to the one under chopping at 0°C for 6 min according to the Raman spectrum analysis. Winter‐type silver carp and Alaska pollock are close in thermal stability (Tironi et al, ).…”
Section: Resultsmentioning
confidence: 71%
“…The temperature of the summer surimi elevated in a higher rate than that of winter surimi. However, S o values of the summer surimi basically demonstrated a tendency of continuous increase, suggesting much more energy/higher temperature was required for thermal aggregating of the proteins (Poowakanjana et al, ). Different patterns in the change of S o values from two types confirmed that thermal stability affected the unfolding of fish proteins during chopping process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations